First report of Myroides phaeus bacteraemia identified by Polymerase chain reaction and genetic sequencing - Pérez-Lazo, G. (2020)
We report the first case of Myroides phaeus isolated from blood, causing bacteremia in an immunocompromised patient using the automated MicroScan Walk Away 96 system, followed by bacterial identification by amplification-sequencing of the 16S rDNA. The sequences obtained were compared with the reference sequence of the BLAST ® platform - National Library of Medicine, USA, and the isolation was identified as Myroides phaeus strain with 99.67 % identity in Blast report. In the literature we did not find previous reported cases of infections by this bacterium, however its pathogenic role is still controversial; therefore, this isolation alerts us to carry out an exhaustive surveillance of other possible acquisition routes.